2011
DOI: 10.1128/jvi.01778-10
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of the Abundance of Cytoplasmic Poly(A) Binding Protein in Human Cytomegalovirus-Infected Cells

Abstract: Irrespective of their effects on ongoing host protein synthesis, productive replication of the representative alphaherpesvirus herpes simplex virus type 1, the representative gammaherpesvirus Kaposi's sarcoma herpesvirus, and the representative betaherpesvirus human cytomegalovirus [HCMV] stimulates the assembly of the multisubunit, cap-binding translation factor eIF4F. However, only HCMV replication is associated with an increased abundance of eIF4F core components (eIF4E, eIF4G, eIF4A) and the eIF4F-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…The HCMV-induced increase in EDD1 protein abundance was not accompanied by a detectable corresponding increase in steady-state mRNA levels, whereas the increase in Paip2 protein was only accompanied by a modest increase in mRNA (Fig. 1C), suggesting an underlying post-transcriptional control strategy similar to what we previously defined for PABP1 (Perez et al 2011). Importantly, while reducing PABP1 abundance has been shown to trigger a corresponding decrease in Paip2 and EDD1 levels (Yoshida et al 2006), this is the first demonstration that these factors are coordinately up-regulated.…”
Section: Pabp1 Accumulation Induced By Hcmv Infection Is Accompanied supporting
confidence: 71%
See 1 more Smart Citation
“…The HCMV-induced increase in EDD1 protein abundance was not accompanied by a detectable corresponding increase in steady-state mRNA levels, whereas the increase in Paip2 protein was only accompanied by a modest increase in mRNA (Fig. 1C), suggesting an underlying post-transcriptional control strategy similar to what we previously defined for PABP1 (Perez et al 2011). Importantly, while reducing PABP1 abundance has been shown to trigger a corresponding decrease in Paip2 and EDD1 levels (Yoshida et al 2006), this is the first demonstration that these factors are coordinately up-regulated.…”
Section: Pabp1 Accumulation Induced By Hcmv Infection Is Accompanied supporting
confidence: 71%
“…To ensure that viral mRNAs (which contain 7-methyl guanosine [m 7 G]-capped 59 and 39 polyadenylated termini) effectively compete for limiting translation factors, HCMV infection triggers an increase in the intracellular concentration of key initiation factors, including the cellular polyadenylate-binding protein PABPC1 (PABP1) and the multisubunit cap-binding complex eIF4F (Kudchodkar et al 2004;Isler et al 2005;Walsh et al 2005;Perez et al 2011). Comprised of the cap-binding protein eIF4E and the RNA helicase eIF4A bound to the large molecular scaffold eIF4G, eIF4F complex assembly is regulated on the m 7 GTP cap structure, facilitating 40S ribosome subunit loading onto the mRNA 59 end (Jackson et al 2010).…”
mentioning
confidence: 99%
“…We also examined the expression of eIF4E and eIF4G in the input samples. Here, we reiterate previous findings that both of these proteins are increased in HCMV-infected cells under normal conditions (27). In addition, the data suggest that the levels of both eIF4E and eIF4G are diminished in mock-infected cells as a result of 4E-BP1 depletion and Torin1 treatment.…”
Section: Figsupporting
confidence: 31%
“…8A), which are translated in an eIF4F-dependent manner. We found that several host mRNAs previously shown to require eIF4F for their translation during HCMV infection were translated less efficiently in the presence of Torin1 (31). In contrast, the relative translation efficiency of HCMV mRNAs was for the most part similar in untreated and Torin1-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 72%